Anthropause appreciation, biophilia, and ecophilosophical contemplations amidst a global pandemic. (February 2023) - Kolandai, Komathi; Milne, Barry; McLay, Jessica; von Randow, Martin; Lay-Yee, Roy
Abstract: In 2020, COVID-19 mitigation measures, including lockdowns and travel bans to curtail disease transmission, inadvertently led to an "Anthropause" – a unique global pause to anthropogenic activities. While there was a spike in ecological studies measuring Anthropause effects on environmental indicators, people's experiences of the Anthropause or its potential to inspire change were hardly considered. Hence, we aimed to measure people's appreciation of the environmental outcomes of the Anthropause, ecophilosophical contemplations about the pandemic, and experiences of lockdown-triggered biophilia (human's innate love for and draw towards nature) and test the hypothesis that these experiences would be consistently more prominent among the already environmentally inclined. To that end, we developed and tested three measures on a representative sample of 993 New Zealanders. Anthropause Appreciation received the highest overall mean ratings, followed by Lockdown-Biophilia and Eco-Contemplation. Pre-existing pro-environmental dispositions and behaviours did not consistently influence our three measures as expected. Demographic variables had little influence, while experiences of financial and mental health impacts due to COVID-19 had no influence. We interpreted the limited influence of explanatory variables as indicative of a degree of uniformity in people's experiences. High appreciation of Anthropause benefits suggests that the public may be supportive of policies and ways of living that can lead to similar outcomes post-pandemic – offering environmental policymakers and communicators a basis for action. Ecophilosophical contemplations and biophilic draw among the public suggest an awareness of the significance of the human-nature relationship – offering a symbolic global keystone for communicating and advocating conservation and the many values of pauses in life to connect with nature. Building women's environmental leadership capabilities and the ongoing greening of Christianity may be essential steps for global post-pandemic environmental behaviour transformations. Highlights: We measured COVID-19-related environmental experiences in a representative sample. The ecological benefits of the Anthropause were highly valued by society. There was moderate eco-contemplation and biophilia during the COVID-19 lockdown. Environmental predisposition and demographics had limited influence. These unique COVID-19-related environmental experiences offer a basis for change.